On groups of finite normal rank - Dashkova, O.Yu. (Algebra and Discrete Mathematics, 2002)
In this article the investigation of groups of finite normal rank is continued. The finiteness of normal rank of
nonabelian p-group G is proved where G has a normal elementary
abelian p-subgroup A for which quotient group G/A is isomorphic
to the direct product of finite number of quasicyclic p-groups.